2012
DOI: 10.1093/eurjhf/hfr166
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term severe diabetes only leads to mild cardiac diastolic dysfunction in Zucker diabetic fatty rats

Abstract: AimsType 2 diabetes mellitus (DM) leads to cardiac dysfunction irrespective of hypertension and coronary artery disease; this is called diabetic cardiomyopathy. Here, we investigated the severity of diabetic cardiomyopathy and myocardial remodelling in aged Zucker diabetic fatty (ZDF) rats. Methods and resultsBody weight, blood glucose and glycated haemoglobin (Hb A1c ) levels, and urinary albumin excretion were monitored regularly in ZDF rats (n ¼ 19) and control littermates (n ¼ 19) up to age 45 weeks. ZDF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 36 publications
11
56
0
Order By: Relevance
“…With age, the complications of diabetes worsen and ZDF rats may become more reliant on the use of lipid reserves to meet metabolic and energy requirements. A recent study in ZDF rats [10] suggests that diabetes per se is not a critical factor in the induction of clinically significant complications and hence some other factors related to obesity might have greater impact on cardiovascular abnormalities. Studies have also suggested that prolonged exposure to insulin suppresses mitochondrial biogenesis and function and this may lead to impairment of insulin sensitivity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…With age, the complications of diabetes worsen and ZDF rats may become more reliant on the use of lipid reserves to meet metabolic and energy requirements. A recent study in ZDF rats [10] suggests that diabetes per se is not a critical factor in the induction of clinically significant complications and hence some other factors related to obesity might have greater impact on cardiovascular abnormalities. Studies have also suggested that prolonged exposure to insulin suppresses mitochondrial biogenesis and function and this may lead to impairment of insulin sensitivity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This may partly account for the reduced weight in aged ZDF rats. A recent study by Daniels et al [11] suggests that diabetes per se is not a critical factor in the induction of clinically significant cardiovascular complications and some other factors related to obesity might have greater impact in ZDF rats. Studies have also suggested that prolonged exposure to insulin suppresses the mitochondrial biogenesis and function and this may lead to impairment of insulin sensitivity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the Zucker diabetic rat and db/db mouse models, both of which result from a mutation in the leptin receptor, are unlikely to reflect all the changes observed in human T2DM. Indeed, several differences have been noted between the cardiac phenotype of these models compared with that observed in diabetic patients [32].…”
Section: Discussionmentioning
confidence: 95%